New product and emerging business growth in Kwara State. Issue 3 (11th July 2016) - Oladele, Seun; Oladele, Femi
Abstract : Purpose: – The purpose of this paper is to examine the effect of new product on growth of emerging businesses (EBs) through sales volume and market share. Design/methodology/approach: – The study surveyed 137 EBs in Kwara State. Two hypotheses were formulated and tested using correlation and regression analyses. Findings: – Results show that service industry is dominant among EBs while the manufacturing industry trails. Many EBs are aware of the complexities of new product, its development and contribution to increasing sales volume, market share and ensuring competitive advantage with apparent infrastructural deficiencies. Test results show that there is a significant positive relationship and effect on sales volume and market share. Originality/value: – Encouraging EBs to step up and focus on improving product/service portfolio to transform their fortune is explored giving focus to the benefits of increasing sales volume and market share.